2005
DOI: 10.1103/physrevlett.94.065003
|View full text |Cite
|
Sign up to set email alerts
|

Nondiffusive Transport in Plasma Turbulence: A Fractional Diffusion Approach

Abstract: Numerical evidence of nondiffusive transport in three-dimensional, resistive pressure-gradient-driven plasma turbulence is presented. It is shown that the probability density function (pdf) of tracer particles' radial displacements is strongly non-Gaussian and exhibits algebraic decaying tails. To model these results we propose a macroscopic transport model for the pdf based on the use of fractional derivatives in space and time that incorporate in a unified way space-time nonlocality (non-Fickian transport), … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
183
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 249 publications
(187 citation statements)
references
References 14 publications
4
183
0
Order By: Relevance
“…0, this turbulent dispersion is superdiffusive because some structures in the turbulence are relatively static and have large amplitudes relative to the background profile, allowing ions to move large distances through the structures. 36 However, if the fluctuations are reduced below a certain level, c R drops dramatically because the amplitude of the vortex structures is too small for the structures to form connected velocity streamlines between the center and edge of the plasma. This is simply a topological constraint set by the amplitude of the turbulent fluctuations.…”
Section: B Interaction Phasementioning
confidence: 99%
“…0, this turbulent dispersion is superdiffusive because some structures in the turbulence are relatively static and have large amplitudes relative to the background profile, allowing ions to move large distances through the structures. 36 However, if the fluctuations are reduced below a certain level, c R drops dramatically because the amplitude of the vortex structures is too small for the structures to form connected velocity streamlines between the center and edge of the plasma. This is simply a topological constraint set by the amplitude of the turbulent fluctuations.…”
Section: B Interaction Phasementioning
confidence: 99%
“…2, 3, 4, 5, 6, 7, 8, 9, 10, applications and enhancements of these techniques were presented. The relevance of fractional calculus in the phenomenological description of anomalous diffusion has been discussed within applications of statistical mechanics in physics, chemistry and biology [11,12,13,14,15,16,17] as well as finance [18,19,20,21,22]; even human travel and the spreading of epidemics were modeled with fractional diffusion [23]. A direct Monte Carlo approach to fractional Fokker-Planck dynamics through the underlying CTRW requires random numbers drawn from the Mittag-Leffler distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Although these assumptions are reasonable and physical realizable, recent experiments and numerical simulations have shown that there are cases in which fluctuations in turbulent plasmas exhibit Lévy statistics. For example, Lévy statistics has been observed in electrostatic edge turbulence in tokamaks and stellarators [11], and in numerical simulations of pressure-gradient driven plasma turbulence [12]. …”
mentioning
confidence: 99%